ANALISIS KEBUTUHAN PENGEMBANGAN LKPD BERBASIS ETNOSAINS TERKAIT MAKANAN KHAS KAWALU KETUPAT AIR TANJUNG UNTUK SD - Rizka Amalia; Ghullam Hamdu; Erwin Rahayu Saputra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Abstrak This study aims to analyze the need for the development of ethnoscience-based Student Worksheets (LKPD) related to the traditional food Ketupat Air Tanjung in elementary science learning. The research method used is descriptive qualitative with data collection techniques including LKPD analysis, interviews with teachers and students, and document studies. The results show that the LKPD used in elementary schools is still conventional, monotonous, and lacks interactivity. Most LKPDs consist only of question collections without exploratory activities that can enhance students' creativity and critical thinking skills. Additionally, the available LKPDs have not systematically integrated science concepts with local culture. Teachers and students expect the development of more engaging, contextual, and local culture-based LKPDs to improve students' understanding of scientific concepts and introduce local wisdom in learning. Thus, the development of ethnoscience-based LKPD is a relevant solution to enhance the quality of elementary science learning.